Vertebral destruction in an 11-month-old child with spinal tuberculosis: a case report and review of literature - Ana Karen Leos-Leija; José Ramón Padilla-Medina; Pedro Martín Reyes-Fernández; Víctor M. Peña-Martínez; Fernando Félix Montes-Tapia; José I. Castillo-Bejarano (SpringerOpen, 2022)
Abstract Background The incidence of tuberculosis is increasing especially in endemic countries. Spinal tuberculosis represents nearly the 50% of reported cases of skeletal tuberculosis. This is the youngest case of spinal tubercular disease that has been reported. The objective of this report is to describe a spinal tuberculosis case in an infant in thoracic spine, in order to show the importance of early diagnosis in this population, to limit the progression of this highly destructive disease and reduce the severe sequelae that this disease is associated. Case presentation An 11-month-old infant previously healthy born in the northeast Mexico. Physical examination revealed a mass lesion in the dorsal region, fixed to deep planes, indurated. Neurological examination found Frankel C paraparesis showing muscle strength 2/5 on the Lovett scale in both lower extremities, anal reflex present, and preserved sensitivity. In the magnetic resonance of the spine, hyperintensities in the vertebral bodies of D6-D9 were observed in the T2 with destruction of the D7 and D8 bodies. A thoracotomy was performed with total mass resection with corpectomy of vertebrae D7 and D8, medullary decompression, and placement of fibula allograft between vertebrae D6 and D9. In the histopathological sample, a chronic granulomatous inflammatory process associated with acid-fast bacilli was observed, in addition to presenting a positive result in quantitative real-time PCR GeneXpert MTB/RIF sensitive to rifampicin. Twelve months later, he presented 5/5 muscular strength, without alterations in sensitivity, in addition to presenting ambulation onset at 18 months of age. Conclusion The spinal tuberculosis is a disease that occurs in endemic countries. A prompt diagnosis is necessary to limit the progression of a highly destructive disease. In addition, the fact of presenting at an early age produces hard making decisions for the adequate treatment of the disease and reduces the adverse effects of these procedures.